Exploring the Effectiveness of Science Training Program on the Performance of Science Teachers at Secondary School Level of Khyber Pakhtunkhwa. - Ahmad, Shakeel; Khan, Rahim (Dialogue (Pakistan))
The study was carried out to check the role of training need, training content, teacher performance, instructional strategies and training assessment on training effectiveness. The research study utilized mixed method approach. A total of 710 science teachers from all the seven divisions and 26 districts of Khyber Pakhtunkhwa were trained, therefore all the 710 science teachers of the Secondary/ higher secondary Schools in all districts of Khyber Pakhtunkhwa constitute the population of this research study. The study was restricted to 248 science teachers as stated in the table given by Krejcie(Krejcie and Morgan 1970). SSTs are categorized as SST(General) and SST(Science); SST(science) is further classified in two categories namely SST(Mathematics-Physics) and SST(Biology-Chemistry). Training was conducted by PITE in 2016, with the assistance of DFID and ASI for both the science categories i.e. SST(Mathematics-Physics) and SST(Biology-Chemistry). These science teachers were selected randomly out of the defined population for the study using simple random sampling. The questionnaire was applied to gather data from the participants in the post training areas. For data collection five point's Likert scale questionnaire was used. The primary data was gathered with the help of questionnaire developed for secondary school teachers. The effectiveness of the training was judged from various angles. Findings of the study revealed that training is having positive effect on the performance of teachers in terms of improved knowledge and practical skills about latest instructional and assessment strategies. 88% respondents were found to be satisfied with the training program and agreed that a trained teacher ensures holistic development of the students. The training program was found to have developed knowledge and practical skills as well as aesthetics sense in the teachers and trained them to use low cost materials and AV aids to achieve SLOs. However, the study found dissatisfaction among the respondents about the follow up of the training, the selection of venues and selection criteria of the teachers.